Examples of Use of FRC with Recycled Concrete in Structures. (2016) - Ráček, Václav; Vodička, Jan; Vytlačilová, Vladimíra
Abstract: By simple production of fibre reinforced concrete, which is designed only from one fraction concrete recyclate, elected doses binders, synthetic fibers and water, the material with characteristics suitable for practical use in selected support structures can be obtained. These results from substantiating tests of production and testing of fibre reinforced concrete this only confirmed. In the paper, the current possibilities of use this structural material is presented. A detailed example of its use for load-bearing walls of buildings of civil construction is shown. A specific calculation of assessment of the building is based on the results of the experimental tests of strength characteristics. Reliability of designed parts of load-bearing structures is based on the design values which are derived from the results of substantiating tests. The given example shows that it is entirely realistic, from the perspective of static reliability, to realize some load-bearing constructions for buildings of community facilities from fibre reinforced concrete, where natural stone is fully replaced by natural recycled material. Although static reliability is the most important parameter it is apparent from this allowance, that in case of use of fibre reinforced concrete in civil construction, it will be necessary to extend the experimental research to other physical properties (eg. heat and sound conductivity).